2017
DOI: 10.1093/infdis/jix275
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Seasonality of Respiratory Syncytial Virus in the United States: The Impact of Increased Molecular Testing

Abstract: Background In the United States, the seasonality of respiratory syncytial virus (RSV) has traditionally been defined on the basis of weeks during which antigen-based tests detect RSV in >10% of specimens (hereafter, the “10% threshold”). Because molecular testing has become more widely used, we explored the extent of polymerase chain reaction (PCR)–based RSV testing and its impact on determining the seasonality of RSV. Methods We assessed antigen- and PCR-based RSV reports submitted to the National Respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 23 publications
4
97
0
Order By: Relevance
“…virus, human coronavirus, and human respiratory syncytial virus (RSV) clearly show peak incidences in the winter months (leading to them sometimes being called winter viruses) (14,(27)(28)(29)(30)(31). Conversely, adenovirus, human bocavirus, human metapneumovirus (hMPV), and rhinovirus can be detected throughout the year (all-year viruses) (30)(31)(32).…”
Section: Seasonality Of Respiratory Viruses In the Human Populationmentioning
confidence: 99%
“…virus, human coronavirus, and human respiratory syncytial virus (RSV) clearly show peak incidences in the winter months (leading to them sometimes being called winter viruses) (14,(27)(28)(29)(30)(31). Conversely, adenovirus, human bocavirus, human metapneumovirus (hMPV), and rhinovirus can be detected throughout the year (all-year viruses) (30)(31)(32).…”
Section: Seasonality Of Respiratory Viruses In the Human Populationmentioning
confidence: 99%
“…So far, epidemiological studies had identified at least nine viruses categories that are capable of infecting respiratory tract [41,42]. Although all feature seasonal oscillation of outbreaks, only three viruses show peak incidences in the winter months, which are the Influenza, human coronavirus, and human respiratory syncytial virus [43,44]. Although the epidemiological characteristics of SARS-CoV-2…”
Section: Discussionmentioning
confidence: 99%
“…A caveat in our method of defining the RSV season is the use of the RSV antigen test as a marker for infection. A recent study found that utilizing PCR as an alternative diagnostic tool allows for a more expanded RSV season and, as a result, an increase in the RSV cases reported [32].…”
Section: Discussionmentioning
confidence: 99%